Prevalence of asthma among norwegian elite athletes - Støle Melsom, H.; Randa, A.; Hisdal, J.; Stang, J. S.; Stensrud, T. (Translational Sports Medicine, 2022)
Objective. Asthma is a common problem among elite athletes and represents a health risk interfering with the athlete`s performance status. This study aimed to evaluate the asthma prevalence among Norwegian summer and winter elite athletes and asthma prevalence across sport categories. We also aimed to examine whether bronchial hyperresponsiveness (BHR), lung function, fraction of exhaled nitric oxide (FENO), and allergy status differed between asthmatic and non-asthmatic elite athletes. Methods. Norwegian athletes qualifying for the Beijing Olympic Summer Games 2008 (n = 80) and the Vancouver Olympic Winter Games 2010 (n = 55) were included. The athletes underwent clinical respiratory examination including lung function measurement, methacholine bronchial challenge for assessment of BHR, FENO, and skin prick testing. Asthma was diagnosed based on respiratory symptoms and clinical examination including objective measurements. Results. Asthma was more prevalent among winter athletes (50%) than summer athletes (20%). Thirty-three (52%) endurance athletes, 3 (6%) team sport athletes, and 7 (33%) technical sport athletes had medically diagnosed asthma. Significantly lower lung function (p < 0.001) and higher prevalence of severe BHR (p < 0.001) were found in asthmatic athletes compared with non-asthmatic athletes. Conclusion. Asthma is common among Norwegian elite athletes, with winter and endurance athletes showing the highest prevalence. Asthmatic athletes were characterized by lower lung function and more severe BHR compared with non-asthmatic counterparts. The high prevalence among winter and endurance athletes demonstrates a need for increased attention to prevent and reduce the prevalence of asthma among those athletes.